Implementation of BTTC image compression algorithm using fuzzy technique - Prasad M.V.N.K.; Shukla K.K.; Mukherjee R.N. (My University, 2025)
This paper presents a new algorithm for image compression based on fuzzy domain decomposition, which is an improvement of the recently published Binary Tree Triangular Coding (BTTC) algorithm. The algorithm is based on recursive decomposition of the image domain into right-angled triangles arranged in a binary tree and uses a fuzzy measure of image compactness. The algorithm executes in O(nlogn) time for encoding and o{barred}(n) time for decoding, where n is the number of pixels in the image. Simulation results on standard test images show that the new algorithm produces significantly less triangles as compared with conventional BTTC while providing the same quality of reconstructed image as good as BTTC. Further, the fuzzy algorithm is more robust with respect to noise. Both these algorithms have faster execution time than JPEG. © Springer-Verlag Berlin Heidelberg 2002.